ANALYSIS OF STUDENTS' PRIOR KNOWLEDGE THROUGH THE MAKE AND MATCH METHOD ON THE SUBJECT OF KHULAFAUR RASYIDIN AT MAN 1 MANDAILING NATAL - Laila Nur Sahara; Dina Dwi Putri; Nurul Mutiah; Syamsiah Depalina Siregar (STKIP Pesisir Selatan, 2026)
Students' prior knowledge is an important factor in determining learning success, especially in Islamic Cultural History (SKI) subjects that require an understanding of historical concepts and values. This study aims to analyze students' prior knowledge through the application of the Make and Match method on the Khulafaur Rasyidin material at MAN 1 Mandailing Natal. The study uses a descriptive qualitative approach with 32 students in class X-K as subjects. Data were collected through learning observations, interviews, and documentation. The Make and Match method is applied once at the initial stage of learning before the delivery of material to map the readiness and initial understanding of students. The results of the study show that the students' prior knowledge is diverse and tends to be factual, with most students only knowing the names of the Khulafaur Rasyidin figures. An interesting finding shows that the application of the Make and Match method can increase student activity, interaction, and cooperation, including among students who were previously passive, making this method effective as an initial strategy for active and contextual SKI learning.